Wychowanie moralne w kontekście przemian cywilizacyjnych - Filipczuk, Marek (Collectanea Theologica, 2018)
The ecclesiastical context appears to have a special importance for moral education. This is obvious as moral education is carried out in the life of a specific religious community. The second half of the 20th century, i.e., the period introducing us into the new millennium, has been a time of deep transformations in Christianity and particularly in the Catholic Church. Needless to say, these transformations have had a remarkable impact on the process of moral education of the young generation. It may be said that the political, economic, social, cultural and religious changes of the 20th century have a specific character. A symptomatic feature of these changes, observed especially nowadays, is their rapid pace as well as their universal character. Industrial civilization transformed not only people’s external living conditions, but has had an influence on man’s inner life and on his behaviour in both moral and religious spheres. The occurrence of these changes can be noted not only in particular nations, but indeed in the whole of mankind. The new conditions exert an influence also on religious life. On the one hand they enhance the ability of a critical judgment and have a purifying effect on the world outlook, ridding it of magical elements and occasional superstitions which happen to darken it. On the other hand there is required a more personal and active clinging to faith, which helps many people to adopt a more vital relationship with God; many others, however, practically abandon religion.